(untitled) (Boston, 2001)
TAKING SIDES: UNITED STATES HISTORY SINCE 1945 presents current controversial issues in a debate-style format designed to stimulate student interest and develop critical thinking skills. Each issue is thoughtfully framed with an issue summary, an issue introduction, and a postscript. An instructor’s manual with testing material is available for each volume.
Keywords: United States,Nước Mỹ; History,Lịch sử; 1945-,1945-